Sifilis sekunder pada seorang remaja perempuan: laporan kasus - Ida Ayu Uttari Priyadarshini; Elice Wijaya; Ni Made Dwi Puspawati (Intisari Sains Medis, 2021)
Introduction: Syphilis is one of the most common sexually transmitted infections worldwide. Syphilis can be acute to chronic. Syphilis is caused by the parasite Treponema pallidum (T. pallidum). Transmitted through sexual contact and blood. In this case, we report a case of secondary syphilis in an adolescent girl.Case report: an 18-year-old girl came with complaints of red spots on the palms of the hands and soles of the feet, with a history of sores in the pubic area that were painless and odorless and then healed on their own so no treatment was given. A history of positive sexual contact approximately one week before the patient came for examination. On dermatological status, right and left palmar and plantar locations found erythematous macules, round to geographical in shape with diameters of 0.5 cm - 1.5 cm and 0.5 cm x 0.7 cm - 0.7 cm x 1 cm, scattered discrete and localized distributions. The patient was differentially diagnosed with secondary syphilis with syphilitic roseola, pityriasis rosea and palmoplantar psoriasis. To confirm the diagnosis, a serological examination was carried out on June 10th 2020, Venereal disease research laboratory test (VDRL) examination with reactive results with a titer of 1:32 and reactive treponema pallidum hemagglutination assay (TPHA) with a TPHA titer of 1:2560. He was given a single dose of intramuscular (IM) injection of benzathine penicillin G 2.4 million international units (IU) and education on further follow up for VDRL laboratory test.Conclusion: A case of secondary syphilis with manifestations of syphilitic roseola has been reported in an 18-year-old teenager. The patient's has a generally good prognosis because in general the patient's condition is good, but considering the patient is still a teenager, it is possible to have irresponsible sexual relations later in life.  Pendahuluan: Sifilis merupakan salah satu penyakit infeksi menular seksual yang sering ditemukan. Sifilis dapat berbentuk akut hingga kronis. Sifilis disebabkan oleh parasit Treponema pallidum (T. pallidum). Menular melalui kontak seksual dan darah. Pada kasus ini dilaporkan sebuah kasus sifilis sekunder pada remaja perempuan.Laporan kasus: remaja perempuan 18 tahun datang dengan keluhan bercak-bercak kemerahan pada telapak tangan dan telapak kaki, dengan riwayat luka pada daerah kemaluan tidak nyeri dan tidak berbau kemudian sembuh sendiri sehingga tidak dilakukan pengobatan. Riwayat kontak seksual positif kurang lebih satu minggu sebelum pasien datang melakukan pemeriksaan. Pada status dermatologi, lokasi palmar dan plantar dekstra et sinistra ditemukan makula eritema, berbentuk bulat hingga geografika dengan ukuran diameter 0,5 cm - 1,5 cm dan 0,5 cm x 0,7 cm – 0,7 cm x 1 cm, tersebar diskret dan distribusi lokalisata. Pasien didiagnosis banding dengan sifilis sekunder dengan roseola sifilitika,  pitiriasis rosea dan palmoplantar psoriasis. Untuk menegakkan diagnosis dilakukan pemeriksaan serologis pada tanggal 10 Juni 2020 yakni pemeriksaan VDRL dengan hasil reaktif dengan titer 1:32 dan TPHA reaktif dengan titer TPHA 1:2560. Diberikan terapi injeksi benzatin penisilin G 2,4 juta international unit (IU) intramuskular (IM) dosis tunggal dan edukasi pemantauan pengobatan yang akan dilakukan yakni pemeriksaan VDRL ulang pada bulan ke-1 setelah terapi.Simpulan: Telah dilaporkan satu kasus sifilis sekunder dengan manifestasi roseola sifilitika pada remaja berusia 18 tahun. Prognosis pasien adalah dubia ad bonam karena pada umumnya kondisi pasien baik, namun mengingat pasien masih remaja, ada kemungkinan untuk melakukan hubungan seksual yang tidak bertanggung jawab di kemudian hari.